PRELIMINARY RESULTS OF ELECTROPHORETIC STUDIES ON MARINE PRAWNS - Thomas, M M (Indian Journal of Fisheries, 2011)
Electrophoretic separation of tissue proteins of fish and prawns has beengenerally acclaimed as a promising technique for the detection of populationunits (Johnson et al 1974). This technique has been found useful in answeringquestions on systematics or population genetics in penaeid prawns of the Gulfof Mexico (Lester 1979).